Environmental Education and Curriculum Theory - Payne, P.G.
Recent reviews of environmental education (EE)research converge with pedagogical trends in the education literature to situated and constructivist learning and the need for greater researcher reflexivity about the assumptions and conduct of research. These trends also elaborate the need in EE and education for sustainable development and related fields of curriculum inquiry and theory for learners to critically examine their own and others' experiences of the various places they regularly encounter. In this article, the author describes a humanly constructive approach to inquiry. This curriculum of 9 questions can be used in its entirety or selectively infused into existing curriculum and pedagogical and research efforts. Because the questions focus on learners' everyday experiences of environmentally problematic and enabling circumstances, this different perspective of curriculum theory reiterates those historical imperatives for experiential, problem (re)solving, interdisciplinary, and participatory action strategies.
Keywords: CURRICULUM THEORY; EMBODIMENT; ENVIRONMENTAL EDUCATION (EE); EXPERIENCE; INQUIRY; PHENOMENOLOGY; SITUATED LEARNING